STRUCTURAL-SEMIOTIC APPROACH TO DEFINITION OF THE SYSTEM ARTISTIC AND PEDAGOGICAL KNOWLEDGE (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the problem of using structure-semiotic approach to the determining of system o f art-pedagogical knowledge and perspective of its further research.